Bayesian Estimators of Dynamic Cumulative Residual Entropy for Pareto Type II Distribution - Savita,; Kumar, Rajeev (Communications in Mathematics and Applications, 2022)
In this paper, Pareto type II distribution is used to propose Bayes estimator of dynamic cumulative residual entropy. To calculate posterior risks, various informative and non-informative priors are used. Using different loss functions, Bayes estimators and associated posterior risks for the distribution have been calculated. Numerical computation is carried out with the help of a real data set. In the last, Monte Carlo Simulation study and Graphical analysis are also given along with the conclusion drawn.